ANALISIS HUKUM MANAJEMEN STRATEGIK KESELAMATAN PASIEN DI RUMAH SAKIT - Dhian Tyas Utami; Feronica Melinda Muskitta; Fanny Fardiyani; Purwadhi; Widjaja, Yani Restiani (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
Strategic Management of Patient Safety is a crucial aspect in modern hospital operations. This study aims to legally analyze Strategic Management of Patient Safety in hospitals through a literature review. In a legal context, patient safety refers to efforts made by hospitals to prevent and reduce the risk of medical errors and ensure optimal patient care. The literature review highlights various legal aspects that are relevant to Strategic Management of Patient Safety. These include the hospital's legal obligation to provide appropriate standards of care, patients' rights regarding information and consent to medical procedures, and the hospital's legal responsibility in handling complaints and claims related to medical errors. The legal analysis also highlights the role of government regulations and policies in encouraging improved patient safety in hospitals. Clear regulations and consistent law enforcement are important factors in increasing accountability and transparency in medical practice. This study provides a deeper understanding of how legal aspects affect Strategic Management of Patient Safety in hospitals. The implications of this analysis can help develop more effective policies and practices in ensuring patient safety and well-being as a top priority in health services.